Structure and Engineering of Francisella novicida Cas9 - Hirano, Hisato; Gootenberg, Jonathan S; Horii, Takuro; Abudayyeh, Omar O; Kimura, Mika; Hsu, Patrick D; Nakane, Takanori; Ishitani, Ryuichiro; Hatada, Izuho; Zhang, Feng; Nishimasu, Hiroshi; Nureki, Osamu (Cell, 2016)
The RNA-guided endonuclease Cas9 cleaves double-stranded DNA targets complementary to the guide RNA and has been applied to programmable genome editing. Cas9-mediated cleavage requires a protospacer adjacent motif (PAM) juxtaposed with the DNA target sequence, thus constricting the range of targetable sites. Here, we report the 1.7 Å resolution crystal structures of Cas9 from Francisella novicida (FnCas9), one of the largest Cas9 orthologs, in complex with a guide RNA and its PAM-containing DNA targets. A structural comparison of FnCas9 with other Cas9 orthologs revealed striking conserved and divergent features among distantly related CRISPR-Cas9 systems. We found that FnCas9 recognizes the 5'-NGG-3' PAM, and used the structural information to create a variant that can recognize the more relaxed 5'-YG-3' PAM. Furthermore, we demonstrated that the FnCas9-ribonucleoprotein complex can be microinjected into mouse zygotes to edit endogenous sites with the 5'-YG-3' PAM, thus expanding the target space of the CRISPR-Cas9 toolbox.